Evaluating the Impact of Sowing Time on Phenology and Yield Attributes in Chickpea (Cicer arietinum L.) Germplasm Accessions under Normal and Late Sown Conditions - Vyshnavi, R. G.; Samaiya, R. K.; Babbar, Anita; Behera, Karishma; Ramakrishnan, R. Shiv (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted during the rabi seasons (November) of 2021– (April) 2022 and 2022 (November) –2023 (April) in Jabalpur, Madhya Pradesh, India aimed to explore chickpea germplasm responses to high temperature stress under varied sowing conditions. Thirty-two germplasm lines and eight elite varieties were sown under normal and late conditions to coincide with heat stress occurrence (>32°C). The investigation done on phenological data impacted by sowing dates, revealed significant differences between normal and late sowing conditions across critical growth stages. Temporal disparities resulted in an approximate 8-day reduction in days to 50% flowering (DFF), 7 days in days to pod formation (DPF), 9 days in days to seed formation (DSF), and 12 days in days to field maturity (DFM). Conversely, longer-duration genotypes experienced a reduction of around 6 days in DFF, DPF, DSF, and 14 days in DFM. Yield attributes among genotypes varied significantly between different sowing conditions. Under normal (D1) conditions, genotypes exhibited adequate seed yield (kg/ha-1), while late-sown (D2) conditions resulted in considerable percentage decrements of 40.2% reduction in the yield. Post hoc Duncan’s New Multiple Range Test (DNMRT) analysis indicated substantial variability among genotypes for all traits, except for primary and secondary branches, observed across both sowing conditions. The correlation analysis uncovered nuanced associations between phenological stages and yield attributes, emphasizing the complexity of chickpea cultivation dynamics. This study provides valuable insights into optimizing chickpea germplasm for high temperature stress resilience, contributing to the ongoing efforts for sustainable and climate-resilient agriculture.